Application of the Walkability Concept to the Yos Sodarso Road Corridor - Mardika Beach Road, Ambon City - Willem Dominggus Nanlohy*; Risal Rasyid (Universitas Syiah Kuala, 2023)
The Ambon City Center area is one of the areas with a fairly high pedestrian intensity. One of the road corridors that has high activity is the Jalan Yos Sudarso - Jalan Pantai Mardika corridor. This corridor is dominated by port activities as well as trade and services. The high level of activity has not been fully balanced with the provision of adequate pedestrian facilities. This study aims to conduct a study on the Application of the Walkability Concept on the Yos Sudarso Street - Mardika Beach Road Corridor in Ambon City, so that increasing community mobility related to walking activities can be properly accommodated. The research method used in this study is quantitative method. This study began by identifying the condition of the pedestrian path based on the Walkability variable, then gave a score using the Likert scale with an assessment guide referring to the Walkability Surveys In Asian Cities. The output of this study is to find that the walkability index value in this corridor is 55, which means that some activities in this corridor can be reached on foot and can also be interpreted that the corridor has walkable potential.